Neuroprotective Effect of Vitamin E in a Kainate-Induced Rat Model of Temporal Lobe Epilepsy - Kiasalari, Z.; Khalili, M.; Roghani, M. (Нейрофизиология, 2014)
Temporal lobe epilepsy (TLE) is known as the most common form of epilepsy in adults and as the type most resistant to treatment. Neuroprotective treatments are considered as a promising therapy for preventing and treating TLE. We investigated the possible neuroprotective effect of vitamin E in an intrahippocampal kainate model of TLE in rats. Kainate injection caused a higher incidence rate of seizures, and vitamin E pretreatment significantly attenuated this index. Intrahippocampal kainate also led to elevation of the malondialdehyde and nitrite/ nitrate levels and lowered superoxide dismutase (SOD) activity, while vitamin E significantly restored MDA and SOD indices. In addition, intrahippocampal kainate induced a significant degeneration of neurons in the CA1, CA3, and hilar regions of the hippocampus; vitamin E considerably attenuated these changes. Timm staining data demonstrated mossy fiber sprouting (MFS) in the dentate gyrus of kainate-lesioned rats, and vitamin E significantly lowered the MFS intensity. Our data suggest that vitamin E pretreatment is capable of attenuating seizures and inhibiting hippocampal neuronal loss and MFS in the kainate-induced model of TLE. A part of the beneficial vitamin E effects is due to its potential to mitigate oxidative stress.